Avaliação de sistemas lipidicos nanoestruturados utilizados como estratégia para melhorar as propriedades biofarmaceuticas do praziquantel no tratamento da esquistossomose - Santos, Fernanda Kolenyak dos [UNESP] (2014)
Schistosomiasis is an infection caused by an intravascular parasite Schistosoma. In Brazil is estimated at 2.5 million the number of people infected by the disease. Praziquantel (PZQ) is the only drug used for the treatment of schistosomiasis and is effective in all kinds of Schistosomes , but shows some features which limit their use, such as, low water solubility and low or erratic bioavailability . The solid lipid nanoparticles (SLNs) are colloidal systems which have been developed by combining the advantages of emulsions, liposomes and polymeric nanoparticles are composed of a matrix that is solid at room or body temperature. Despite the well-described SLNs have some characteristics that limit their use, such as, ease of expulsion of the drug during storage, and the amount of encapsulated drug in the matrix limited. To overcome these limitations, a new class of nanoparticles was developed, named nanostructured lipid carriers (NLCs), which are composed of a matrix containing a mixture of solid and liquid lipid. In This study we aimed to develop both systems as a strategy to improve the efficacy of PZQ. Systems have been developed employing the method of mixing in high shear rate and were characterized by average particle diameter, zeta potential, polydispersity index using photon correlation spectroscopy, encapsulation efficiency, differential scanning calorimetry (DSC), thermogravimetry analysis (TGA), x-ray diffraction, electron microscopy (SEM), nuclear magnetic resonance (NMR), infrared spectroscopy (IR). The safety profile was assessed through studies of cellular cytotoxicity, hemolysis of erythrocytes. The in vitro and in vivo activity of both systems (SLN and NLC) were evaluated. The results for all systems exhibited a diameter of 165 to 653nm , and the zeta between -21 to - 40mV and the polydispersity index was between 0.385 to 694 , the systems presented a high encapsulation efficiency between 83 % to 92 % , indicating that a ...